Lack of association between 11 gene polymorphisms on weight loss 1 year after Roux‐en‐y gastric bypass surgery in woman. Issue 4 (29th March 2022) - Novais, Patrícia Fatima Sousa; Crisp, Alex Harley; Leandro‐Merhi, Vania Aparecida; Verlengia, Rozangela; Rasera, Irineu; de Oliveira, Maria Rita Marques
Abstract: Background: Although effective, the impact of bariatric surgery on weight loss is variable, and little is known about the influence of single‐nucleotide polymorphisms (SNPs). The present study investigated the association of eleven SNPs related to obesity with weight loss 1 year after Roux‐Y gastric bypass (RYGB) surgery in female patients. Methods: This prospective study included 351 women with obesity. The genotypes for eleven SNPs ( GHRL –rs26802; GHSR– rs572169; LEP– rs7799039; LEPR– rs1137101; 5HT2C– rs3813929; UCP2– rs659366; UCP3– rs1800849; SH2B1– rs7498665; TAS1R2– rs35874116; TAS1R2– rs9701796; FTO– rs9939609) were determined using a real‐time polymerase chain reaction and TaqMan assays. Anthropometric measurements were performed before and 1 year after RYGB surgery. To evaluate the factors that influenced the proportion of weight loss 1 year after surgery, beta regression analysis was used. The models were estimated using the GLIMMIX procedure in SAS statistical software. p  < 0.05 was considered statistically significant. Results: The mean ± SD percentage of total body weight loss in 1 year was 64.4 ± 5.8% and the median was 65.0%. When assessing the proportion of weight loss in 1 year after surgery, using univariate analysis (beta regression), no SNPs influenced weight loss. Furthermore, in the multiple analysis, with stepwise process of variable selection, no variable was significant to compose the multiple model. Conclusions: The 11 SNPs investigated did not influence weight loss 1 year after RYGB surgery in female patients. This result indicates that individual behaviours and other factors might better contribute to the magnitude of loss weight loss in a short period after bariatric surgery. Key points: None of the 11 single‐nucleotide polymorphisms (SNPs) investigated from the univariate beta regression showed a significant influence on the proportion of weight loss 1 year after Roux‐Y gastric bypass (RYGB) surgery. Our main finding indicate that the SNPs investigated are not related to weight loss during the first year of RYGB surgery. This enhances the importance of behavioural and environmental variables in the outcome of the surgery because the main obesity‐related genes were considered here. This research indicates that individual behaviours and other factors might better contribute to the magnitude of loss weight loss in a short period after bariatric surgery.